Co-Management Supervision Ad-Hoc Against Ombudsman Audit-Based Disaster Assistance Fund Together with Disaster Victims - Anwar, Arman; Daties, Dyah R.A.; Tahamata, L.C.O. (International Journal of Psychosocial Rehabilitation, 2020)
The main problem in this research is when a disaster occurs in Indonesia, there will also be a corruption case of the disaster assistance fund. One of the reasons is the ineffective management of supervision and the unresponsive mechanism of reporting / complaints from disaster victims. Therefore, the aim of this research is to find an effective and responsive monitoring and reporting model to prevent corruption of disaster funds. This research was conducted using the Social Legal Research method. The problem approach uses a statutory, case and concept approach. The results of this study found that to prevent the occurrence of maladministration of public services that have the potential for criminal acts of corruption is to improve management supervision and reporting / complaints mechanisms. Research concludes that this can be overcome by opening up space for the participation of disaster victims to become an integral part of surveillance management. Their rights should not be passively limited to reporting, but must be actively involved in auditing with the Ombudsman. The study recommends a co-management model of ad hoc supervision of the Ombudsman audit-based disaster fund together with the disaster victims community. The involvement of disaster victims with the principle of participation, transparency and accountability in making every decision related to their interests is their constitutional rights as citizens, especially since disaster affected communities are an important part of the target implementation of the program